Analysis of wind-induced response of down lead transmission line-connection fitting systems in ultrahigh-voltage substations. (1st March 2020) - Zhang, Meng; Shang, Ruhao; Lu, Zhongbin; Zhang, Xizhuo; Xie, Kai; Zhang, Bo
Highlights: Behavior of high-voltage bushing terminal with connection fitting was investigated. Reasonable shape of the DLTL system was proposed and validated. Dynamic amplification factor for engineering design of bushing terminal was proposed. Factors inducing the failure of the seal of the bushing were revealed. Abstract: Based on a certain 1, 000-kV ultrahigh-voltage substation, a finite element model is established for the down lead transmission line (DLTL)-connection fitting system using the ABAQUS software. The mechanical properties of the bushing terminal and the connection fitting under equivalent static loads corresponding to various wind speeds are analyzed. The analytical results are compared with experimental results to verify the correctness of the model. On this basis, the effects of the connection fitting type, the DLTL system type and the suspension location of the DLTL system on the mechanical properties of the bushing terminal are discussed. The dynamic response of the DLTL-connection fitting system to various wind speeds is investigated through simulation. The results are as follows. From a mechanical perspective, the bushing terminal with an "I"-shaped connection fitting is notably superior to that with a "U"-shaped connection fitting; however, the "I"-shaped connection fitting system must be strengthened. Compared to the " λ "-shaped DLTL system that is currently and commonly used, the " π "-shaped DLTL system is more reasonable, but the offset of its suspension point must be controlled (0–3 m is recommended). When considering the vibration caused by pulsating winds, the maximum stress on the bushing terminal increases significantly, and premature failure is risked. In engineering design, a dynamic amplification factor no less than 2.0 is recommended for use to consider this adverse effect.